Recolonization : GATT, the Uruguay Round & the Third World - Raghavan, Chakravarthi; Nyerere, Julius K. (London: Zed Books; Penang, Malaysia: Third World Network, 1990)
"Chakravarthi Raghavan ; foreword by Julius Nyerere Bibliotheek François Vercammen"